Tulane Engineering Is Latest Katrina Victim. - Jones, W.D.
2007 will be the last year that Tulane University students earn degrees in computer science, electrical, mechanical, and civil engineering. The programs, say the administration, were jettisoned in the interest of keeping the rest of the New Orleans university afloat. The remaining engineering disciplines - chemical and biomedical engineering - have been subsumed into a conglomeration being called the School of Science and Engineering.
Keywords: Hurricane Katrina; New Orleans; School of Science and Engineering; Tulane University; Civil engineering; Computer science; Electrical engineering; Engineering; Mechanical engineering